Utilization Of Organic Fertilizer From Cocoa Shells Waste (Theobroma cacao L) and Soy Milk Dregs (Glycine max L) on The Growth of Red Spinach (Amaranthus tricolor L) - Ismul Mauludin Al Habib; Fatimatuz Zuhro (BIO-CONS : Jurnal Biologi dan Konservasi, 2021)
Waste of cocoa shells and soy milk dregs can cause environmental pollution. In fact, both of these wastes contain quite high macro and micro nutrient content which has the potential to increase plant and soil fertility. This study aims to utilize cocoa shells waste and soy milk dregs as organic fertilizer for the growth of red spinach. This study used a randomized block design (RBD) with 5 treatments, namely; P0 (control), P1 (1 gram of urea as positive control), P2 (70 grams of cocoa shells fertilizer), P3 (300 grams of soy milk dregs fertilizer), and P4 (a combination of cocoa shells fertilizer and soy milk dregs fertilizer). The parameters observed, among others; plant height, number of leaves and plant wet weight. The results of data analysis showed that there were significant differences between treatments P0, P1, P2, P3 and P4. Treatment P4 gave the best effect on the growth of red spinach plants among other treatments.